(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Red cell distribution width (RDW) is a routinely reported hematological parameter traditionally used in the evaluation of anemia. In recent years, it has gained attention as a potential biomarker of systemic inflammation, oxidative stress, and cardiometabolic dysregulation. Elevated RDW has been associated with adverse cardiovascular outcomes, metabolic disorders, and chronic inflammatory states, highlighting its emerging role as a simple, cost-effective prognostic and risk-stratification marker. Objective: To investigate the association between RDW and metabolic risk parameters, including fasting blood glucose and lipid profile components, in an adult population using routine laboratory data. Methods: A retrospective observational analysis was performed on 250 adult laboratory records. RDW values were analyzed in relation to fasting blood glucose, total cholesterol, triglycerides, and high-density lipoprotein cholesterol. Age- and gender-based differences were assessed using appropriate statistical methods. Results: The mean RDW was 13.43 ± 0.90%. RDW demonstrated a strong positive correlation with fasting blood glucose (r = 0.524) and moderate positive correlations with total cholesterol (r = 0.380) and triglycerides (r = 0.274), while showing a significant inverse correlation with high-density lipoprotein cholesterol (r = −0.218) (all p < 0.001). RDW values increased significantly with advancing age (p < 0.001). No statistically significant gender-related differences were observed. Conclusion: RDW was significantly associated with adverse metabolic profiles and increases with age, supporting its potential utility as a low-cost adjunct marker for cardiometabolic risk assessment in routine clinical practice. Further prospective studies are warranted to establish its prognostic significance in cardiovascular disease.